An Eclectic Theory of Entrepreneurship: Policies, Institutions and Culture - Ingrid Verheul; Sander Wennekers; David Audretsch; Roy Thurik (Tinbergen Institute, 2001)
The level of entrepreneurship differs considerably across countries and periods. Both thecauses and consequences of entrepreneurship are a matter of extensive scientific debate aswell as of great policy importance. A high level of entrepreneurial activity is assumed andshown to contribute to innovative activities, competition, economic growth and job creation.The present paper deals with the determinants of entrepreneurship. An eclectic theory ofentrepreneurship is introduced. This eclectic theory provides an integrated framework,drawing on disparate strands of literature, to create a better understanding of the different rolethat entrepreneurship plays in different countries and time periods. This framework isdesigned to guide future empirical research in this area and to provide insights forpolicymakers striving to promote entrepreneurship.
Keywords: 330; Entrepreneurship-Ansatz; Theorie der Unternehmung; Theorie